Landscaping Crossover Interference Across a Genome. (October 2017) - Sun, Lidan; Wang, Jing; Sang, Mengmeng; Jiang, Libo; Zhao, Bingyu; Cheng, Tangran; Zhang, Qixiang; Wu, Rongling
Abstract : The evolutionary success of eukaryotic organisms crucially depends on the capacity to produce genetic diversity through reciprocal exchanges of each chromosome pair, or crossovers (COs), during meiosis. It has been recognized that COs arise more evenly across a given chromosome than at random. This phenomenon, termed CO interference, occurs pervasively in eukaryotes and may confer a selective advantage. We describe here a multipoint linkage analysis procedure for segregating families to quantify the strength of CO interference over the genome, and extend this procedure to illustrate the landscape of CO interference in natural populations. We further discuss the crucial role of CO interference in amplifying and maintaining genetic diversity through sex-, stress-, and age-induced differentiation. Trends: COs between two homologous chromosomes during meiosis promote genetic diversity, and are regulated by three machineries, (i) obligate CO formation, (ii) CO interference, and (iii) CO homeostasis. CO interference, a phenomenon where the occurrence of one CO prevents the formation of another CO nearby, is detected traditionally by genetic mutation screening. The identification of CO interference can also be through multipoint analysis. By designing various sampling strategies based on biological properties of species, this approach can be widely used to estimate and test CO interference for both experimental and natural populations. Multipoint analysis, that is traditionally used to construct genetic linkage maps, provides a means to detect and quantify CO interference, thereby providing new insights into the mechanistic basis of genome evolution in eukaryotes.